Peran Guru PAI dalam Meningkatkan Kedisiplinan Siswa Melaksanakan Salat Berjamaah di SMKN 1 Hiliran Gumanti - Zakia, Yulita; Murniyetti, Murniyetti (YASIN, 2023)
This research is motivated by the current reality in which there are many negligence among teenagers in carrying out prayer services. Therefore, schools must have the habit of praying in congregation, so that the younger generation instills good habits from an early age. This study focused on the role of Islamic Religious Education teachers in increasing the discipline of students in carrying out congregational midday prayers at SMKN 1 Hiliran Gumanti with the following problem formulation: 1) The role of Islamic Religious Education teachers in increasing the discipline of students carrying out congregational prayers at SMKN 1 Hiliran Gumanti 2) Factors supporting and inhibiting factors of Islamic religious education teachers in increasing the discipline of students in carrying out congregational prayers. To achieve this goal using qualitative methods with a descriptive approach. This research was conducted at SMKN 1 Hiliran Gumanti. Data collection techniques used are observation, documentation and interviews. The results of this study indicate that: (1) The role of the Islamic Religious Education teacher is to provide good examples and examples to students, through habit, giving advice and also giving punishment to students who are not disciplined in carrying out midday prayers in congregation (2) Supporting factors for teachers Islamic Religious Education in disciplining congregational midday prayers, namely the existence of good cooperation between Islamic religious education teachers and other teachers, and the existence of school policies. And the inhibiting factors for Islamic Religious Education teachers in disciplining congregational midday prayers are inadequate ablution facilities, inadequate prayer rooms, frequent water problems and lack of awareness of students to carry out congregational midday prayers.